One year work experience in a municipal Intensive Therapy Unit. - Alba Enseñat Alvarez; Rubén Bembibre Taboada; Julio Jova Dueñas; Angel Luis Valladares Delgado; José Roque Nodal; Luis Orlando Iturralde González (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
Background: The Municipal Intensive Care Units were created in the year 2004, to better the urgency attention in the primary health level. Objective: To characterize the functioning of a Municipal Intensive Care Unit. Method: A descriptive, prospective study that included 348 patients that were received in the unit during the year 2004. The following variables were analized: patients evolution, distribution by diseases, and evolution of the diseases. Results and Conclusions: The number of remissions to the hospital dropped; 183 patients weresent to their homes, 165 were remitted to the Provincial Hospital of Cienfuegos and three of them died in the unit. The angina pectoris was the first cause of admission, followed by cardiac arritmias and cerebrovascular disease.